Green Energy And Economic Growth Dynamics - Arnolds Efimovičs Kims; Juris-Roberts Kalniņš; Alijanov Donyorbek Dilshodovich; Topvoldiyev Nodirbek Abdulhamid o‘g‘li (Stanford Database Library of American Journal of Applied Science and Technology, 2026)
The global transition to green energy has transformed renewable technologies into fundamental drivers of economic growth, industrial modernization, and national resilience. This study examines the economic mechanisms through which green energy contributes to macroeconomic performance by integrating a modified Cobb–Douglas production function, Leontief input–output analysis, and comparative institutional assessment. Using multi-source data from the International Energy Agency (IEA), the International Renewable Energy Agency (IRENA), the OECD, the World Bank, and Bloomberg New Energy Finance, the study evaluates the impacts of renewable deployment on capital formation, employment dynamics, supply chain complexity, green finance expansion, and energy security. The results demonstrate that renewable energy adoption reinforces total factor productivity and stimulates high-value industrial clusters, including photovoltaic systems, wind turbines, hydrogen production, battery energy storage systems (BESS), and smart microgrids. These clusters exhibit significant backward and forward linkages, generating manufacturing spillovers, skilled job creation, and technological innovation. The findings also indicate that green finance instruments—particularly green bonds, ESG-compliant investment, and carbon pricing frameworks—play a central role in mobilizing private capital and accelerating renewable deployment. Moreover, the diversification of the energy mix reduces dependence on imported hydrocarbons, thereby enhancing strategic autonomy and macroeconomic stability. Overall, the study concludes that green energy should be interpreted not merely as an environmental asset but as a strategic economic catalyst of the twenty-first century. Its contribution extends across economic, financial, industrial, and geopolitical domains, suggesting that countries capable of successfully integrating renewable energy into their industrial and financial architectures will secure stronger competitive advantages, more diversified economic structures, and more resilient development trajectories.